The Unpredictable Errors of Micro Tactile Metrology – Factors Affecting Stylus tip Contamination - Kinnell P.; Habeb R. (Measurement Science Review, 2013)
In 3D tactile micro-metrology the contamination of probing devices is a major problem that affects the accuracy and repeatability of measured dimensions. Despite a large body of research in the field of micro CMM and micro probe design there is limited research which has been done so far to explain and tackle this problem. In this work, experimental probing on a range of materials using a micro coordinate measuring machine was conducted to investigate the mechanism of stylus tip contamination. In addition the effects of surface finish on the build-up of stylus tip contamination were also studied. The results provide practitioners with guidelines which allow for the likely build-up of stylus tip contamination to be minimized based on sample material type and surface finish.